Enhancing Grade 7 Reading Proficiency through an English Reading Program Intervention in High School - Bendo, Mhel Cedric D.; Angue, Dhanna Driff; Buhay, Jeraldine; Dimaisip, Jeizel Anne; Lobos, Tracy Lobos; Pahimnayan, Ellie Grace; Piedad, Raj Benedict; France Lawrence Pulgo, France Lawrence; Ramos, Karylle; Yabut, Whinzel Anne (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
This study aimed to determine the level of reading proficiency of Grade 7 students through the implementation of an English Reading Program at Public National High School, Philippines. A  quantitative  one-group pretest–posttest design was employed, involving 494 Grade 7 students across eleven sections. Data were gathered using validated standardized reading comprehension assessments administered before and after the intervention. Findings revealed that the English Reading Program was effective in improving students’ reading proficiency. Post-test results showed a notable increase in reading comprehension levels, with no students classified as non-readers after the intervention. The use of contextualized learning materials contributed to measurable improvements in students’ ability to decode, comprehend, and interpret texts. Overall, the study provides evidence-based support for the effectiveness of structured reading intervention programs in enhancing reading proficiency among junior high school learners. The findings offer practical implications for school administrators and teachers and highlight the importance of targeted reading programs in improving academic performance and promoting the overall well-being of Grade 7 students.
Keywords: Reading Proficiency; Reading Intervention; English Reading Program; Grade 7 Learners; Philippine Education; Reading Comprehension